Effects of Temperature, UV Radiation, and Soaking Time (in Drinking Water) to Histidine-Bentonite Adsorbentâs Performance - Anna Permanasari (Institut Teknologi Bandung, 2009)
Bentonite material modified by amino acid (amino-bentonite) is a save adsorbent for drinking water management. It can be used to adsorb organic/pesticides residues from water. Amino-bentonite adsorbed organic/pesticides residue pollutants in the water effectively. Histidine-bentonite is one of amino-bentonites that has successfully synthesized, and was proven as the effective adsorbent and showed high capacity of pesticides adsorption. Effects of temperature, UV radiation, and soaking time (in drinking water) to histidine-bentonite adsorbents performance has been examined utilizing UV, FTIR, XRD , and SEM techniques. The result showed that histidine-bentonite stable in 25-30 oC range of waters temperature, unstable to UV radiation, and could not be soaked in water more than a week because of the faster bacteria growth than without histidine-bentonite it self.